THE IMPACT OF TEACHERS' GENDER DIFFERENCES ON CLASSROOM MANAGEMENT - Doğa Oktan; Çağda Kıvanç Çağanağa (Informascope, 2015)
Teachers perceive classroom management as one of the most crucial and enduring aspects in education. This study aims to explore impacts of female and male teachers on classroom management at European University of Lefke. The study also intends to investigate the differences between the classroom management strategies of an experienced female EFL teacher and an experienced male EFL teacher. Qualitative method was used for data collection and data analysis. Reflected reports were required from a male and a female teacher. In addition, semi-structured interviews were conducted to the same male and female teachers. Results indicate that there is no significant difference on the classroom management according to the genders of the teachers. Keywords: Gender, female, male, classroom management